Canadian Bitcoin ownership in 2023: Key takeaways - Daniela Balutel; Marie-Hélène Felt; Doina Rusu (Bank of Canada, 2025)
We provide an update on cryptoasset ownership in Canada using data from the Bitcoin Omnibus Survey conducted in late 2023. Bitcoin ownership remained stable at around 10% in 2023 and continues to be concentrated among men, younger individuals and those with higher income and levels of education. The use of Bitcoin for payments remains limited, with most owners viewing it primarily as an investment. Despite growing awareness of alternative cryptocurrencies, Bitcoin remains the dominant holding among Canadians, with a median value of Can500.
Keywords: E4; C81; O51; 330; Bank notes; Digital currencies and fintech; Econometric and statistical methods